The Effects of Multipropped Deep Excavation-Induced Ground Movements on Adjacent High-Rise Building Founded on Piled Raft in Sand - Mukhtiar Ali Soomro; Naeem Mangi; Wen-Chieh Cheng; Dildar Ali Mangnejo (Advances in Civil Engineering)
In this paper, a three-dimensional numerical parametric study was conducted to predict the deformation mechanism of a 20-storey building sitting on a (4 × 4) piled raft to an adjacent 25 m deep basement excavation. The influences of different excavation depths were investigated. An advanced hypoplastic sand model (which is capable of taking small-strain stiffness into account) was adopted to capture soil behaviour. The computed results revealed that excavation adjacent to a building resting on the piled raft caused significant settlement, differential settlement, lateral deflection, and interstorey drift in the building. With settlement due to working load (i.e., 4.8dp%), the total settlements of the building (7.8dp%) exceed the maximum allowable foundation settlement (i.e., 50 mm). In addition, substantial bending moment, shear forces, and changes in axial load distribution along pile length were induced. The findings from this study revealed that the building and pile responses are significantly influenced by the excavation depth.